Joyfull: Cook Effortlessly, Eat Freely, Live Radiantly - Devlukia-Shetty, Radhi ([New York] : Simon Element, 2024)
"More than 125 plant-based recipes and a practical approach to making deeply flavorful food for feeling your best."--Provided by publisher.
Keywords: Vegetarian cooking; Vegan cooking; Cookbooks